Peran Bimbingan Konseling dalam Meningkatkan Efektivitas Konsultasi dan Kolaborasi di SMA Negeri 3 Kota Tasikmalaya - Ari Rahmat Hidayat; Feida Noorlaila Isti’adah (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
This study aims to describe in depth the role of guidance and counseling (BK) in improving the effectiveness of consultation and collaboration services at SMA Negeri 3 Tasikmalaya City. Consultation and collaboration services are an integral component of the BK program that focuses on professional interactions between BK teachers and various related parties, such as subject teachers, homeroom teachers, parents, and other stakeholders who are concerned about student development. Through these services, BK teachers help students overcome personal, social, and academic problems holistically. This study used a qualitative approach with descriptive methods. Data were collected through in-depth interviews, participant observation, and documentation analysis to obtain a comprehensive picture of the consultation and collaboration practices implemented. The data analysis process was carried out thematically to identify interaction patterns, forms of collaboration, and supporting and inhibiting factors in the implementation of services. The results show that BK teachers at SMA Negeri 3 Tasikmalaya City play an active role as a communication liaison between students, teachers, and parents, as well as mediators in solving problems faced by students. Effective collaboration between BK teachers and all related parties contributes to the creation of a conducive, inclusive, and responsive learning environment to students' needs. Consultation services implemented in a planned, continuous, and data-driven manner can provide a better understanding of student problems and offer appropriate and applicable alternative solutions. These findings confirm that guidance and counseling play a strategic role in supporting educational success in schools. The implementation of effective consultation and collaboration services not only positively impacts student problem-solving but also strengthens synergy between educational elements in building a supportive school climate oriented toward student well-being.